Engaging banality - Kuroi, Senji,Tillack, Peter (Brill, 2017)
Preliminary Material /Kuroi Senji – Introduction: Engaging Banality – Hole and Sky /Kuroi Senji and Peter Tillack – Time /Kuroi Senji and Peter Tillack – Running Family /Kuroi Senji and Peter Tillack – Index. Engaging Banality: Stories of the Salaried Life by Kuroi Senji features three of the best-known works of Kuroi Senji’s early career. H́ole and Sky\' (1968), Time (1969) and Running Family (1970) received widespread critical attention in Japan and have been reprinted many times, yet none has been translated until now. In its own way each story reveals the profound ambivalence increasing numbers of Japanese began to feel toward their lives as their desires were channelled into the nation’s single-minded goal of achieving high-speed economic growth. The stories are preceded by a critical introduction that situates Kuroi’s development and ethos as a writer within the context of profound socio-cultural change spanning the end of World War II through the early 1970s
Includes index
Keywords: Japanese fiction